2009
DOI: 10.1167/9.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Can illumination estimates provide the basis for color constancy?

Abstract: Objects hardly appear to change color when the spectral distribution of the illumination changes: a phenomenon known as color constancy. Color constancy could either be achieved by relying on properties that are insensitive to changes in the illumination (such as spatial color contrast) or by compensating for the estimated chromaticity of the illuminant. We examined whether subjects can judge the illuminant's color well enough to account for their own color constancy. We found that subjects were very poor at j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…It is beyond our purpose to test precisely how well observers could perceive the illumination. Experiments that have tested observers' conscious perception of the illumination have failed to find a veridical percept (Granzier et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is beyond our purpose to test precisely how well observers could perceive the illumination. Experiments that have tested observers' conscious perception of the illumination have failed to find a veridical percept (Granzier et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the changes between subsequent illuminants were quite evident to the observers. We did not use familiar objects in the scene for two reasons: First, one study found that the presence of familiar objects does not significantly lead to better matches of the illumination (Granzier et al, 2009a), and second, another study showed that the presence of familiar objects does not significantly help in achieving color constancy . The latter study was still important, as Granzier and colleagues (2009a) showed that there is no correlation between conscious estimates of the illumination and color constancy performance.…”
Section: The Scenementioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that a model based on the gray world assumption (e.g., [1]) would fail to predict the effect of chromatic orientation, since it only relies on the mean chromaticity in the scene. There are a number of studies, however, in which the chromatic distribution of the visual scene is probed to derive information about the chromaticity of the illuminant (e.g., [2,[29][30][31][32]). But even if we suppose that this would result in the correct estimation of the exact illuminant color, it would still not predict that one illuminant leads to a higher color fidelity than another.…”
Section: Discussionmentioning
confidence: 99%